TINJAUAN KELENGKAPAN PENGISIAN PERSETUJUAN TINDAKAN KEDOKTERAN DI PUSKESMAS KECAMATAN PANCORAN - Indah Kristina; Bramentyo Bagas Rahardja (MEDICORDHIF Jurnal Rekam Medis, 2022)
Bramentyo Bagas Rahardja, Review of Completeness of Completion of Approval of Medical Action at Pancoran Subdistrict Health Center, Jakarta, Scientific Paper, Diploma-III Program of the Bhumi Husada Academy of Medical Records and Health Information, Jakarta 2021, VI BAB, 73 pages, 6 Tables, 3 Attachments. The consent form for medical action must be filled 100% completely. Because medical action can carry a high risk and must obtain the consent of the patient or patient's family. By completing the medical action consent form, it can avoid claims that cause things that have the potential to pay compensation. The purpose of this study was to determine the completeness of filling out the approval for medical action at Pancoran District Health Center. In this study the authors used descriptive research methods, namely research methods carried out with the main aim of making a description of the completeness of filling out the approval of medical action at the Pancoran District Health Center. Based on observations made by the author in September 2020, it was found that the consent form for medical action was incomplete, of the 30 forms that were observed all were not 100% complete, the highest incompleteness was in the authentication section by 85%. The population of this study, namely all forms of approval for medical action in December 2020 to February 2021, counted as many as 365 forms, then the sample was calculated using the Slovin formula and the sample results obtained were 191 Medical Action Approval Forms, after analysis and results were found that were completely filled. with a percentage of 91% or as many as 175 forms of approval for medical action and not completely filled in with a percentage of 9% or as many as 16 forms of approval for medical action. This means that the Pancoran Subdistrict Health Center is not yet good at completing the completion of the medical action approval Bibliography 16 (1991 - 2018) Keywords: Completeness of Filling in Approval of Medical Action